Sistem Sosial dan Kepercayaan Masyarakat Terhadap Paham Towani Tolotang di Kabupaten Wajo - Kaharuddin, Kaharuddin (Universitas Muhammadiyah Makassar, 2017)
This study aims to explain the conception of public confidence in religious values towani towani tolotang in wajo district. The research method used is qualitative descriptive approach with data collection techniques, observation, interview and documentation. The result of my research shows that the religious conception of towani tolotang people as a believer or belief that believes in God is considered as a divine equivalent of God Almighty as the belief of Muslims who created the universe and its contents. this seuwae god is also deployed as a patotoe that determines the fate of man. Humans as social beings who always need interaction and socialization. Towani tolotang as a religious community has its own norm of social interaction, and the norms prevailing in their society are binding, with rules to adhere to.Keywords: Social System, Trust, Towani Tolotang